Accuracy of cortical bone trajectory screw placement in midline lumbar fusion (MIDLF) with intraoperative cone beam navigation - Laratta, Joseph L. (J Spine Surg, 2019)
BACKGROUND: Cortical bone trajectory (CBT) screws have been recently described as a method of lumbosacral fixation. These screws are typically inserted under fluoroscopic guidance with a medial-to-lateral trajectory in the axial plane and a caudal-to-cephalad trajectory in the sagittal plane. In an effort to reduce surgeon radiation exposure and improve accuracy, CBT screws may be inserted under navigation with intraoperative cone beam computed tomography (CT). However, the accuracy of CBT screw placement under intraoperative navigation has yet to be assessed in the literature. The purpose of the study was to evaluate the accuracy of CBT screw placement using intraoperative cone beam CT navigation. METHODS: One hundred and thirty-four consecutive patients who underwent CBT fixation with 618 screws under intraoperative navigation were analyzed from May 2016 through May 2018. Screws were placed by one of three senior spine surgeons using the Medtronic O-Arm Stealth Navigation. Screw position and accuracy were assessed on intraoperative and postoperative CT scans using 2D and 3D reconstructions with VitreaCore software. RESULTS: The majority of surgeries were primary cases (73.1%). The mean age at the time of surgery was 61.5±10.0 years and the majority of patients were female (61.2%). Most patients underwent surgery for a diagnosis of degenerative spondylolisthesis (47.8%) followed by mechanical collapse with foraminal stenosis (22.4%). Ten violations of the vertebral cortex were noted with an average breach distance of 1.0±0.7 mm. Three breaches were lateral (0.5%) and seven were medial (1.1%). The overall navigated screw accuracy rate was 98.3%. The accuracy to within 1 mm of error was 99.2%. There were no intra-operative neurologic, vascular, or visceral complications related to the placement of the CBT screws. CONCLUSIONS: CBT screw fixation under an intraoperative cone beam CT navigated insertion technique is safe and reliable. Despite five breaches greater than 1mm, there were no complications related to the placement of the CBT screws in this series.